Correction of temporal wasting using calcium hydroxylapatite with integral lidocaine: An underused procedure for enhancing overall facial appearance - Barbarino, Sheila C. (Journal of cosmetic dermatology, 2021)
Background Hollowing of the temple area is an early sign of aging that is often overlooked, but when corrected, can lead to significant subject and physician satisfaction. Aims To assess physician and subject awareness of the impact of temporal hollowing on appearance and to evaluate treatment satisfaction following injection of calcium hydroxylapatite with integral lidocaine (CaHA(+)). Patients/Methods Subjects with temporal depression grade ≥2 on a validated Temple Hollowing Scale were recruited. CaHA(+) was injected supraperiosteally using a bolus technique. Photographs were taken prior to treatment and 30 days, and graded by three evaluating physicians using the Global Aesthetic Improvement Scale (GAIS) and Temple Hollowing Scale. The same physicians estimated subjects' age before and after treatment. Photographs were graded by patients as part of a satisfaction questionnaire. Results The study enrolled 10 subjects aged 32‐68 years old. Physician GAIS scores of subject appearance at 1 month were rated as “very much improved” in 80% and “much improved” in 20% of subjects. Temple hollows were graded as 1 after treatment in 90% of subjects. Following blinded review of patients' true ages, estimates for subjects' perceived age were on average 4 years younger than their actual age. Most subjects had not been aware of temple hollowing prior to treatment, but nine out of 10 were very to extremely satisfied with results, and all were willing to repeat treatment. No treatment complications were observed. Conclusion Treatment of the temple area can have a dramatic aesthetic effect and should not be neglected when addressing facial rejuvenation. CaHA(+) is an effective and well‐tolerated product for use in the temple area and is associated with a high degree of subject and physician satisfaction.